Effect of Compensation and Organizational Culture on Spirit of Work and Its Impact on Employee Performance at PT Mopoli Raya Medan - Sembiring, Hendri (International Review of Management and Marketing, 2019)
The purpose of this study was to determine the effect of compensation and organizational culture on morale and its impact on employee performance at PT Mopoli Raya Medan. This study used a quantitative descriptive method. The population and sample in this study are permanent employees in all parts of PT Mopoli Raya Medan, amounting to 50 respondents. The sampling technique used is nonprobability sampling. This study uses path analysis which consists of two equations. The results of the study showed two path structural sub-structural equations, namely Y1 = 3.817 + 0.510X1 + 0.300X2 + 0.658 and Y2 = 2.934 + 0.299X1 + 0.352X2 + 0.292Y1 + 0.616. The first sub-structural equation explains that compensation variables and organizational culture have a positive and significant effect on work morale both partially and simultaneously, which partially or directly compensation variables have a more dominant influence on work morale than organizational culture variables with their respective contributions amounting to 0.510 and 0.300. Furthermore, the second sub-structural equation explains that compensation variables, organizational culture, and work morale have a positive and significant effect on employee performance both partially and simultaneously, which partially or directly compensation variables have a more dominant influence on employee performance compared to organizational culture variables and work morale with contributions of 0.510, 0.300 and 0.292 respectively. As well as simultaneous compensation variables, organizational culture and morale influence on employee performance by 62 % and the remaining 38% is influenced by other variables. Keywords: Compensation, Organizational Culture, Spirit of Work, and Employee Performance. JEL Classifications: C30; O15; O25 DOI: https://doi.org/10.32479/irmm.7769